(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
The physicochemical properties of slag are of great importance in pyrometallurgy. The traditional measurements are usually carried out over a long heating period with a sustained high temperature. If there is a volatile component in the slag, evaporation will inevitably occur. As a result, the slag composition will change, and the measured results will be inconsistent with the original slag composition. Therefore, the traditional measurement methods are not suitable for measuring the physicochemical properties of slag with a higher volatile content. To solve this problem, a way that keeps the traditional measuring methods but modifies the slag’s chemical composition to fit the measured data was suggested. Two typical kinds of slag ESR slag with higher CaF2 and Pb smelting reduction slag with higher PbO were chosen, and melting point measurements were taken as an example to demonstrate the new method in practice. Weight loss measurements and evaporation test with thermogravimetric (TG) analysis, as well as high-temperature mass spectrometer (MS) tests were carried out to indentify the volatiles. It was found that CaF2 and MgF2 is the main volatiles with a small amount of AlF3 to ESR slag and PbO is the main volatile with a small amount of ZnO. Based on these points and the weight loss, the slag melting points measured with traditional method and the slag chemical composition were modified to fit the melting point value. The new method can fit Pb smelting slag with a higher PbO well because the evaporation component was almost all PbO. For ERS slag with a higher CaF2, this method was slightly complicated because of the evaporation of several components at the same time. Anyway, this way is proved to be feasible in theory and practice. Some suggestion for further research are proposed. The work will be of significance for both slag and molten salt with volatiles.